Verb Derivations from the Names of Countries and Peoples in the Middle East and Around the World - Ilaiyan, Salman (Journal of Semitic studies, 2013)
This article documents and examines linguistic innovations (neologisms) in Arabic verbs, focussing on verbs derived from nouns referring to the names of geographical locations and peoples in the Middle East and elsewhere around the world. These verbs and their accompanying gerunds were found through a systematic examination of Arabic‐language newspapers (daily, weekly and monthly issues) published in various Arab countries between the years 1994 and 2010. These neologisms have begun to appear in the press in the context of contemporary political developments. The article presents a classification of the different types of verbs derived from geographical locations and peoples in the Middle East, and the socio‐political context in which these words were derived.